Analisis Praktek Akad Qardhul Hasan Dalam Perspektif Ekonomi Syari’ah Di Koperasi Dewan Kemakmuran Masjid At-Taqwa Desa Cicadas Sagalaherang Kabupaten Subang - Mita Nurul Hidayati; Ahmad Damiri; Jalaludin (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2021)
Cooperatives are generally financial institutions that accept deposits and loans for financing, by collecting funds from their members which are then channeled back to members or the general public. This study aims to analyze the application of Qardhul Hasan financing in the perspective of Islamic Economics carried out at the At-Taqwa Mosque Prosperity Council Cooperative, Cicadas Village, Sagalaherang District, Subang Regency. Qardhul Hasan has the meaning of a good loan, the Qardhul Hasan product is a financing offer to customers that will be used for micro businesses, then members return installments according to the nominal borrowed at a predetermined time, and it is very important that we examine how the implementation of Qardhul Hasan in perspective Islamic economics, because lending and borrowing is one part of our lives in the world. This study aims to find out how the provisions and implementation of the Qardhul Hasan contract, the sharia economic perspective on the Qardhul Hasan contract and the impact of the Qardhul Hasan contract on the community. This type of research is qualitative using descriptive analysis method. Sources of data used include primary and secondary data. The results of the analysis show that the implementation of the Qardhul Hasan contract at the At-Taqwa Mosque Prosperity Council Cooperative in Cicadas Village is in accordance with Islamic law. This can be seen where the cooperative provides loans without any additional. In the Qardhul Hasan contract in Cicadas Village there is non-performing financing. the factors are, first, because of the lack of direction and guidance from the cooperative. Second, because of the negligence of the members themselves. The impact that members feel is very helpful for business capital costs, schools, health